Diplodia parva sp. nov., a novel species of the family Botryosphaeriaceae isolated from soil in Korea - Lee, Seung-Yeol; Ten, Leonid N.; Ayim, Benjamin Yaw; Fulbert, Okouma Nguia; Das, Kallol; Jung, Hee-Young (Phytotaxa, 2021)
A fungal strain designated KNU16-007, belonging to the family Botryosphaeriaceae, was isolated from soil in Daegu, Korea. Phylogenetic analyses based on the concatenated nucleotide sequences of the ITS and TEF-1α regions, showed that the isolate resides in a clade together with Diplodia species but occupies a distinct phylogenetic position. Conidial dimensions of strain KNU16-007 (22.7–29.3 μm × 8.9–10.9 μm) or its conidial length:width ratio were significantly differed from those of the closely related D. sapinea, D. intermedia, D. scrobiculata, D. seriata, D. crataegicola, D. rosacearum, and D. citricarpa clearly indicating morphological differences from these species. Detailed descriptions, illustrations, and discussions regarding the morphological and phylogenetic analyses of the closely related species are provided to support the novelty of the isolated species. The results of phylogenetic analysis and morphological observations indicate that strain KNU16-007 represents a novel species in the genus Diplodia, for which the name Diplodia parva sp. nov. is proposed.